The Impact of Artificial Intelligence on Business Strategy: A Review of Theoretical and Empirical Studies in China - Diyin, Zhu; Bhaumik, Amiya (International Journal of Advances in Business and Management Research (IJABMR), 2025)
This review article examines the revolutionary influence that artificial intelligence (AI) has had on corporate strategy in China. It does so by analysing theoretical frameworks and empirical investigations in order to identify significant trends, problems, and possibilities. Businesses are using artificial intelligence technologies such as artificial intelligence, machine learning, and advanced analytics to improve decision-making, streamline operations, and acquire competitive advantages as China ranks as a worldwide leader in AI development. Across several sectors, including finance, retail, healthcare, and manufacturing, the analysis emphasises how artificial intelligence is changing strategic planning, consumer interaction, supply chain management, and product creation. Furthermore, covered is how government policies—including the Next Generation Artificial Intelligence Development Plan—help to create an artificial intelligence-driven commercial environment. The paper also points out difficulties companies have, including data protection issues, skill shortages, and ethical conundrums when incorporating artificial intelligence into their plans. Moreover, it emphasises the cultural and financial elements influencing the use of artificial intelligence in Chinese companies, therefore stressing variations from Western strategies. The paper ends with pointing out gaps in present research and recommendations for further investigations, including the long-term effects of artificial intelligence on sustainable company models, leadership styles, and employment trends. This paper provides insightful analysis for academics, legislators, and corporate executives negotiating the fast-changing technology environment as well as helps to clarify how artificial intelligence is driving strategic change in China's corporate scene.